Rolling the Dice on Foreclosure Prevention: Differences Across Mortgage Servicers in Loan Modifications and Loan Cure Rates. Issue 1 (2nd January 2017) - Reid, Carolina K.; Urban, Carly; Collins, J. Michael
Abstract: Mortgage servicing has garnered increased attention since the foreclosure crisis. As the interface between borrowers and investors, servicers make the decision to either grant a loan modification or to foreclose. This study examines servicer loan modification practices for a national sample of delinquent subprime loans, and assesses the extent to which those practices are associated with foreclosures. The research reveals significant differences across servicers in loan cure rates, which are related to servicers' propensity to offer loan modifications and to the level of relief offered to borrowers. The observed differences across servicers and the implications of this heterogeneity for foreclosure prevention underscore the importance of additional data, research, and policies that can increase the uniformity and transparency of servicing practices.